Transformasi Keuangan Digital dan Partisipasi Anggota TerhadapInklusi Keuangan Digital: Peran Mediasi Kualitas Layanan Keuangan Digital Pada Koperasi Kredit di Kota Ambon - Maria Josefa F Esomar; Evracia Turukay (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the influence of digital financial transformation and member participation on digital financial inclusion, with the quality of digital financial services as a mediating variable in credit unions in Ambon City. This study employed a quantitative causal-associative approach. Data were collected via a questionnaire administered to 150 credit union members who were familiar with or had used digital financial services and were analyzed using Structural Equation Modeling-Partial Least Squares. The results indicate that digital financial transformation has a positive and significant effect on the quality of digital financial services (β = 0.16; p = 0.00) but does not have a direct effect on digital financial inclusion (β = -0.01; p = 0.56). Member participation significantly affects the quality of digital financial services (β = 0.84; p = 0.00) and digital financial inclusion (β = 0.49; p = 0.00). The quality of digital financial services also has a significant effect on digital financial inclusion (β = 0.51; p = 0.00) and mediates the relationship between the variables. These findings indicate that the digitalization of cooperatives cannot be achieved through the provision of technological systems alone; it must be translated into services that are secure, responsive, user-friendly, and supported by participation.